Dermatologic Indicators of Systemic Autoimmune Disease: Clinical Links to Ocular Involvement - Abbas, Hana; Kothari, Zarin; Multani, Harleen; Sraa, Kiratpreet; Imokhai, Ochuwa; Malik, Azka; Kantipudi, Sanjana; Lee, Danny (Dermatology Practical & Conceptual, 2026)
Introduction: Systemic autoimmune diseases frequently involve both the skin and eyes, with early cutaneous manifestations often serving as visible indicators of deeper, multisystem pathology. Conditions such as systemic lupus erythematosus, dermatomyositis, sarcoidosis, and Sjögren’s syndrome display characteristic skin findings, including malar rash, heliotrope eruption, lupus pernio, or xerosis, which may precede or parallel serious ocular complications, including uveitis, retinal vasculitis, conjunctival granulomas, and keratoconjunctivitis sicca. Despite this overlap, diagnostic and therapeutic strategies remain fragmented across specialties. Objectives: By highlighting the clinical intersections between dermatological and ocular manifestations in systemic autoimmune diseases, we aim to promote earlier recognition, integrated treatment, and improved outcomes for patients affected by these multisystem disorders. Methods: This review synthesizes the literature from the last fifteen years, between 2010 and 2025, on four major autoimmune conditions: systemic lupus erythematosus, dermatomyositis, sarcoidosis, and Sjögren’s syndrome. Results: We examine disease-specific immunopathology, diagnostic modalities, and therapeutic strategies, while also discussing the need for interdisciplinary management models, including those that bridge dermatology and ophthalmology. Conclusion: By highlighting these clinical intersections, we aim to promote earlier recognition, integrated treatment, and improved outcomes for patients affected by these multisystem disorders.